2021
DOI: 10.14207/ejsd.2021.v10n2p59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Awareness of University Students: the Case of the University of Presov, Slovakia

Abstract: At present, all components of the environment are burdened by human activities. These human activities have caused many environmental problems, and without appropriate measures, they will have other far-reaching consequences in the future, which may be irreversible. One of the basic measures for the sustainable future of the environment and human society is to build the environmental awareness of the population. In addition to other entities, universities and their students and graduates have an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…Moreover, the above-discussed literature indicated that environmental protective behavior is highly influenced by environmental awareness and climate change awareness [18,32], which, in turn, positively contributes to environmental quality [19,33]. Hence, the present study expects a significant mediating role for environmental protective behavior on the association among environmental awareness, climate change awareness, and environmental quality.…”
Section: Environmental Awareness Environmental Protective Behaviors A...mentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, the above-discussed literature indicated that environmental protective behavior is highly influenced by environmental awareness and climate change awareness [18,32], which, in turn, positively contributes to environmental quality [19,33]. Hence, the present study expects a significant mediating role for environmental protective behavior on the association among environmental awareness, climate change awareness, and environmental quality.…”
Section: Environmental Awareness Environmental Protective Behaviors A...mentioning
confidence: 57%
“…The study indicated that the laborers who were aware of different environmental issues are more likely to engage in eco-friendly behaviors that are very beneficial for environmental quality. Similarity Novotný et al [33] believed that the environment is hampered by human activities. Their study investigated whether humans who are aware of the adverse effects of environmental issues are more likely to engage in eco-friendly initiatives that resultantly improve environmental quality.…”
Section: Climate Awareness and Environment Qualitymentioning
confidence: 60%
See 1 more Smart Citation
“…Este trabajo, por sí mismo, contiene implicaciones pedagógicas evidentes: las estrategias de aprendizaje para alcanzar el aprovechamiento de las actividades relacionadas con el compostaje, promueven en los estudiantes una actitud cívica y una actitud productiva para las instituciones y para la sociedad en general. En relación con el aprovechamiento y manejo de residuos sólidos, así como la participación en proyectos ambientales, los estudiantes mostraron actitudes favorables, como puede comprobarse por su participación en la mayoría de las actividades propuestas, lo cual concuerda con lo encontrado por otros investigadores, en distintos niveles educativos que comprenden desde primaria hasta superior (Asilsoy et al, 2017;Álvarez et al, 2022;Gok y Kilic, 2021;Gutiérrez Sabogal, 2017;Herrera, 2017;Novotny et al, 2021;Scott, y Suisberger, 2019;Stoeva y Alriksson, 2017;Yilmaz et al, 2021). También, indica que, consistentemente, después de la intervención por medio de estrategias didácticas específicas, los alumnos presentaron un cambio de actitud positivo en relación con el tratamiento de residuos sólidos y lograron establecer relaciones entre los problemas ambientales a escala local, con las condiciones que podrían derivar del cambio climático a nivel global.…”
Section: Implicaciones Pedagógicasunclassified
“…Various studies have demonstrated the concern of university students about environmental protection [20][21][22][23][24]. Student awareness signifies developing responsible behavior toward, in this case, soil pollution, based on knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 99%